2005
DOI: 10.1016/j.amjhyper.2004.08.027
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of stress reduction in African Americans treated for hypertension for over one year

Abstract: A selected stress reduction approach, the Transcendental Meditation program, may be useful as an adjunct in the long-term treatment of hypertension in African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 57 publications
1
96
1
3
Order By: Relevance
“…For example, cardiovascular disorders responsive to TM include hypertension and hypercholesterolemia (Schneider et al, 2005). Other medical conditions responsive to meditation include asthma and stuttering, as well as hormonal disorders such as type 2 diabetes, primary dysmenorrhea, and premenstrual syndrome (now called premenstrual dysphoric disorder) (Murphy & Donovan, 1997).…”
Section: Somatic Therapeutic Responsesmentioning
confidence: 99%
“…For example, cardiovascular disorders responsive to TM include hypertension and hypercholesterolemia (Schneider et al, 2005). Other medical conditions responsive to meditation include asthma and stuttering, as well as hormonal disorders such as type 2 diabetes, primary dysmenorrhea, and premenstrual syndrome (now called premenstrual dysphoric disorder) (Murphy & Donovan, 1997).…”
Section: Somatic Therapeutic Responsesmentioning
confidence: 99%
“…22 Transcendental meditation leading to reduction of stress and decrease in BP in was documented in African American hypertensives. 23 Various forms of yoga also claim to reduce stress by integrating the body and mind. 21,24 Other studies evaluating yoga practice suggests that yoga may reduce oxidative stress and endothelial-dependent vasodilatation in patients with established coronary artery disease.…”
mentioning
confidence: 99%
“…Controlling for age produced significant results for TM on SBP when compared to PMR (p<.025) or HE (p<.0005), and for DBP, TM compared to PMR (p<.05) or HE (p<.00005). TM appears to be more efficacious for those who are not on medication, but also simultaneously decreases BP and use of anti-hypertension medication [120], and has been found to reduce the reliance on and desire for drugs in general [121]. A separate subgroup analyses by sex was published by Alexander et al suggested efficacy of TM for treating hypertension in patients in high as well as low risk categories for six hypertension-related measures of risk: obesity, alcohol use, psychosocial stress, dietary sodium-to-potassium ratio, physical inactivity, and presence of multiple risks [82].…”
Section: Impact On Hypertensionmentioning
confidence: 99%
“…In the fourth RCT on TM and blood pressure, Schneider et al [120] collaborated with the Haight-Ashbury Free Medical Clinic supported by an NIH grant extending the earlier threemonth design [97] to one-year. The study randomly assigned 150 hypertensive African Americans (mean age 49 years; mean 142/95 mm Hg) to TM, Progressive Muscle Relaxation (PMR), or Health Education (HE).…”
Section: Impact On Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation